Determinação das características térmicas de um pack de baterias de lítio por meio de simulação multifísica - Rommel, Fabio Junior (2023)
Multiphysics simulation (SM) is a computational procedure capable of solving two or more physical phenomena in the same simulation process. In this work, multiphysics, thermo-electric simulations were carried out with a lithium-ion battery pack model for use in electric vehicles (EV) intended for urban mobility, in Brazil, within the scope of the Rota 2030 project, with a partnership UTFPR, Renault do Brasil and Senai-PR. The thermal management of the batteries is one of the critical factors in the development of a battery pack since if it operates in thermal conditions outside the recommended range, it reduces the useful life of the batteries, and they may even start to burn, a phenomenon known as a thermal runaway. Performing SM is essential to understand the thermal behavior of the battery cells in the pack during use (charge/discharge), in addition to enabling the study of ways to manage energy. The present research carried out thermoelectric simulations of a 25 kWh pack of prismatic lithium-ion batteries of the type NMC-523. Each cell has a nominal capacity of 105 Ah and a nominal voltage of 3.71V. The tool used was Fluent from the ANSYS software platform. Were defined with the aid of the Battery Model toolbox, the Multi-Scale Multi-Domain (MSMD) solution method, and the NTGK electrochemical model (Newman, Tiedemann, Gu, and Kim). The simulations were carried out in a cell, a module with nine cells, and a pack with eight modules, totaling 72 battery cells connected in series. The models were simulated with passive thermal management (natural convection) and models considering a case of phase change material (PCM), with six types of PCM (three paraffin-based and three high-density polyethylene). The thermal profile of the batteries was analyzed for the discharge condition, varying the discharge rates from 0.5 C to 2.0 C. As a result, we obtained the heating curves of the models for each PCM and for each of the conditions simulated discharge. With these curves and with the temperature distribution images on the surface of the models, it was possible to verify the thermal profile of the batteries and the influence of using the PCM case on the final temperature of the battery cells. The main results found with this research were: The use of the PCM case, in the thermal management of the batteries, for the model of module and pack modeled is not efficient in conditions of discharge under little effort (below 2.0 C), presenting; however, greater efficiency for discharges above 2.0 C, in which the effort of discharging the battery is considerably greater.